Star turns and cameo appearances : memoirs of a life among musicians - Jacobson, Bernard (University of Rochester Press, 2015)
Up-close and personal views, by the renowned music critic and orchestra administrator, of musical luminaries from Alfred Brendel to Jessye Norman and beyond.